Global Firms, National Corporate Taxes : An Evolution of Incompatibility - Hebous, Shafik (IMF Working Papers; Working Paper ;, 2020)
How did the rise of multinational enterprises (MNEs) put pressure on the prevailing international corporate tax framework? MNEs, and firms with market power, are not new phenomena, nor is the corporate income tax, which dates to the early 20th century. This prompts the question, what is distinctly new (about multinational enterprises)-if anything-that has triggered unprecedented recent concerns about vulnerabilities in international tax arrangements and the taxation of MNEs? This paper presents a set of empirical observations and a synthesis of strands of the literature to answer this question. A key message is that MNEs of the 21st century operate differently from prior periods and have evolved to become global firms-with important tax ramifications. The fragility of international tax arrangements was present at the outset of designing international tax rules, but the challenges have drastically intensified with the global integration of business, the increased trade in hard-to-price services and intangibles, and the rapid growth of the digital economy.